High endocan levels are associated with the need for mechanical ventilation among patients with severe sepsis. Issue 1 (6th July 2017) - Mangat, Mandeep; Amalakuhan, Bravein; Habib, Sheila; Reyes, Luis F.; Hinojosa, Cecilia A.; Rodriguez, Alejandro H.; Soni, Nilam J.; Anzueto, Antonio; Levine, Stephanie M.; Peters, Jay I.; Aliberti, Stefano; Sibila, Oriol; et al.
Sepsis affects more than 750 000 Americans each year, with a mortality rate close to 30% [1]. A significant amount of resources has been put into improving our understanding of sepsis and developing new therapies. A push for early sepsis recognition and subsequent timely treatment has led to an interest in inflammatory biomarkers to identify sepsis and its severity [2]. Respiratory dysfunction occurs in up to 81% of cases and a significant proportion requires ventilatory support [1]. Studies have looked at a variety of biomarkers, from inflammatory cytokines such as interleukin (IL)-6 to endothelial proteins like intercellular adhesion molecule-1, to identify patients at greatest risk of developing respiratory compromise [3]. Endocan may have a role as a predictive biomarker for need for mechanical ventilation in patients with severe sepsis http://ow.ly/raKd30bSqTk